Case report: A combination of nitroglycerin and adenosine proves effective in repairing a cerebral arteriovenous malformation - Rojas-Nieves, Virginia; Rosa-Carrasquillo, Cristian; Reyes-Sullivan, Allan; Román, Marie; Feliciano-Valls, Caleb E.; Torres-Pérez, Héctor M.; Fernández, Pamela; Crespo, María J. (Frontiers in Neurology, 2023)
Hemorrhage secondary to rupture of a brain arteriovenous malformations (AVM) is one of the initial manifestations, and the main cause of, morbidity and mortality in patients with this condition. Current treatment strategies include endovascular embolization with the goal of AVM obliteration and neurological preservation. In the transvenous endovascular embolization procedure, adenosine is the preferred agent to induce temporary hypotension and allow adequate AVM embolization. We describe the intraoperative management of an adenosine-resistant 38year-old male who underwent a successful intracranial AVM embolization after concomitant administration of gradually increasing doses of nitroglycerin. This report suggests that nitroglycerin infusion can be combined with adenosine boluses to create a pronounced and dosedependent hypotension in patients partially unresponsive to adenosine alone.